The importance aspects of landscape design on housing development in urban areas - Mohd Shahli, FitryNadia; Mohd. Hussain, Mohd. Ramzi; Tukiman, Izawati; Zaidin, Nurbazliah (Elsevier, 2014)
It has been proven that proper landscape planning and designs with the sustainability concept and approach help to create a conducive and responsive environment of housing development. This paper presents a brief of conceptual view on the important aspects of landscape design on housing development in urban areas. The review is based on the theoretical framework of the relationship between landscape design in planning and designing the housing development in urban areas as well as how it acts as an added value to the sustainable residential landscape design. A review on previous researches and journals are doing in providing a theory on the importance aspect of landscape design in housing areas. It is hoped that this paper may possibly provide significant information on landscape design towards influencing the prices and values of the house. This paper also can become an indicator towards enhancing the sustainability of living environment